Isolation and Identification of Antiradical and Anti-photooxidant Component of Aloe vera chinensis - Yohana S. Kusuma Dewi; Tranggono Tranggono; Sri Raharjo; Puji Hastuti (Indonesian Food and Nutrition Progress, 2005)
A potent antiradical and antiphotooxidant compound from Aloe vera chinensis was investigated. The results indicated that the methanolic extracts produced stronger antiradical and antiphotoaxidant activity also gave higher yields of extract than other organic solvents. Silica gel column separated methanolic extracts into five fractions. Of the five fractions, fraction II possessed significant antiradical activity (70.2 % inhibition on free radical DPPH) and its showed significant antiphotooxidant activity (60.1 % inhibition on hydroperoxide formation). Subsequently, fraction II was separated into eight subfractions by silica gel column. The sub fraction II-b exhibited stronger antiradical and antiphotooxidant activity than others and showed a single spot in thin layer chromatography Silica gel 60 F254 plates. On the basis of mass spectrophotometry in combination with reversed phased, high performance chromatography, this compound has been identified as 1,8 dihydroxy-3- hydroxymethylanthraquinone (Aloe emodin).